Physical Activity, Fatigue, and Sleep in People with Parkinson’s Disease: A Secondary per Protocol Analysis from an Intervention Trial - S. Coe; M. Franssen; J. Collett; D. Boyle; A. Meaney; R. Chantry; P. Esser; H. Izadi; H. Dawes (Parkinson's Disease)
Symptoms of Parkinson’s can result in low physical activity and poor sleep patterns which can have a detrimental effect on a person’s quality of life. To date, studies looking into exercise interventions for people with Parkinson’s (PwP) for symptom management are promising but inconclusive. The aim of this study is to estimate the effect of a clearly defined exercise prescription on general physical activity levels, fatigue, sleep, and quality of life in PwP. Method. PwP randomised into either an exercise group (29; 16 males, 13 females; mean age 67 years (7.12)) or a control handwriting group (36; 19 males; 17 females; mean age 67 years (5.88)) as part of a larger trial were included in this substudy if they had completed a 6-month weekly exercise programme (intervention group) and had complete objective physical activity data (intervention and control group). Sleep and fatigue were recorded from self-reported measures, and physical activity levels measured through the use of accelerometers worn 24 hours/day over a seven-day testing period at baseline and following the 24-week intervention. A Wilcoxon’s test followed by a Mann–Whitney post hoc analysis was used, and effect sizes were calculated. Results. Participants showed a significant increase in time spent in sedentary and light activities during the overnight period postintervention in both exercise and handwriting groups (p<0.05) with a moderate effect found for the change in sedentary and light activities in the overnight hours for both groups, over time (0.32 and 0.37-0.38, resp.). There was no impact on self-reported fatigue or sleep. Conclusion. The observed moderate effect on sedentary and light activities overnight could suggest an objective improvement in sleep patterns for individuals participating in both exercise and handwriting interventions. This supports the need for further studies to investigate the role of behavioural interventions for nonmotor symptoms.